Performance assessment of subsea safety systems subject to heterogeneous failure modes and repair delays - Dan, Emefon; Liu, Yiliu (Frontiers in Energy Research, 2024)
Subsea production systems operate in harsh and hostile environment making them subject to degradation which leads to failure. This is also the case for the final elements of safety instrumented systems (SISs) that installed for protecting subsea production systems.As a result the classic performance assesment methods of SISs that assume constant failure rates may not be realistic for subsea elements, which may experience both random failures and natural degradation. The location of subsea production also provides challenges for accessing the system to perform repair, this often results in delays before repair following revealed failures. In this paper, we explore all these issues by developing formulations that incorporate degradation and random failures as well as repair delays to assess the performance of the system. The degradation of the system is modelled with the Weibull distribution while the exponential distribution is used to model the random failures. The impacts of different maintenance strategies on safety are also explored with case studies.